AKUNTABILITAS PEMERINTAH DESA DALAM PENGELOLAAN ALOKASI DANA DESA DI DESA TEMULUS KECAMATAN MEJOBO KABUPATEN KUDUS - Firdha Ayu Pramesti; Teguh Yuwono (Journal of Politic and Government Studies, 2018)
This study aims to determine and describe the Accountability Village Government in the Management of Village Allocation Fund in the Temulus Village including of planning, implementation, supervision, and accountability and how about community responds to Village Government in Management of Village Allocation Fund. This research is done because Village Allocation Fund is one form of government responsibility to promote development in the village and Temulus village is an developing village. This study used a mixed methods, it contain qualitative method and quantitative method. As mixed method, with focus on collection, analyzing, and mixed about qualitative and quantitative in a single or plural research. The sample in this study amounted to 95 people and interviewees to 5 people involved in fund management accountability village. Results of research conducted about planning procees system is good, like example about community’s respond that positive who attends the village discussion, then for  implementation of have implemented the principles of transparency and accountability. Supervision composed with internal and external, while the accountability of Allocation of village funds (ADD) both technically and administration is good, but it must given more excercise to village government that involved in fund management accountability village.Keywords: Village Allocation Fund (ADD), Planning, Implementation, Supervision, and Accountability